Comprehensive clinical and epidemiological assessment of colonisation and infection due to carbapenemase-producing Enterobacteriaceae in Spain. Issue 2 (February 2016) - Palacios-Baena, Zaira R.; Oteo, Jesús; Conejo, Carmen; Larrosa, M. Nieves; Bou, Germán; Fernández-Martínez, Marta; González-López, Juan José; Pintado, Vicente; Martínez-Martínez, Luis; Merino, María; Pomar, Virginia; Mora-Rillo, Marta; et al.
Summary: Background: Most available information on carbapenemase-producing Enterobacteriaceae (CPE) is usually associated with specific types of infection or patient or with descriptions of outbreaks. The aim of this study was to comprehensively analyse the clinical epidemiology, clinical features and outcomes of colonisation and infections due to CPE in Spain. Methods: A multicentre prospective cohort study was carried out in 34 Spanish hospitals from February to May 2013. All new patients testing positive for CPE in clinical samples were included. Logistic regression was used to identify predictors of mortality. Results: Overall, 245 cases were included. The most frequent organism was Klebsiella pneumoniae (74%) and the carbapenemases belonged to the OXA-48 (74%), metallo-β-lactamase (MBL) (24%) and KPC (2%) groups. Acquisition was nosocomial in 145 cases (60%) and healthcare-associated (HCA) in 91 (37%); 42% of the latter were nursing home residents, in whom OXA-48-producing K. pneumoniae ST405 predominated. MBLs and OXA-48 predominated in ICU and medical patients, respectively. Overall, 67% of patients had infections. The most frequent infections identified in this study were urinary tract (43%) and skin structure (21%) infections, and 10% of infections were bacteraemic. Crude mortality was 20%. Inappropriate antibiotic therapy was independently associated with an increased risk of death (OR = 3.30; 95% CI: 1.34–8.11). Conclusions: We found some differences in the epidemiology of CPE depending on the type of carbapenemase produced. Although a low proportion of CPE infections were bacteraemic, active antibiotic therapy was a protective factor for reducing mortality. Highlights: OXA-48-producing Enterobacteriaceae were associated with community-onset, healthcare acquisition. Metallo-β-lactamase (MBL) producers occurred more frequently in ICU patients. OXA-48-producers caused urinary tract infection more frequently than MBL producers. Only 10% of infections were bacteraemic. Non-active targeted therapy was independently associated with increased mortality.